2012
DOI: 10.1001/archgenpsychiatry.2011.1528
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Behavior Therapy for Adults With Tourette Syndrome

Abstract: Context Tics in Tourette syndrome begin in childhood, peak in early adolescence, and often decline by early adulthood. However, some adult patients continue to have impairing tics. Medications for tics are often effective but can cause adverse effects. Behavior therapy may offer an alternative but has not been examined in a large-scale controlled trial in adults. Objective To test the efficacy of a comprehensive behavioral intervention for tics in adults with Tourette syndrome of at least moderate severity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
287
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 282 publications
(301 citation statements)
references
References 37 publications
12
287
2
Order By: Relevance
“…Wilhelm and colleagues studied adults with GTS and found that those receiving CBIT demonstrated significant reductions and tics and tic-related impairment at the end of acute-phase treatment relative to supportive therapy. Gains were maintained for post-treatment responders at the 6-month follow-up 152 . In both studies, adverse events were tracked, and none were associated with CBIT.…”
Section: Thoughts For Dougmentioning
confidence: 98%
See 1 more Smart Citation
“…Wilhelm and colleagues studied adults with GTS and found that those receiving CBIT demonstrated significant reductions and tics and tic-related impairment at the end of acute-phase treatment relative to supportive therapy. Gains were maintained for post-treatment responders at the 6-month follow-up 152 . In both studies, adverse events were tracked, and none were associated with CBIT.…”
Section: Thoughts For Dougmentioning
confidence: 98%
“…Implemented in 8, structured 60-90 minute sessions over 10 weeks, this comprehensive behavioural intervention for tics (CBIT) 151 was tested through two large randomised controlled trials 89,152 . Both studies compared CBIT to a psychoeducation and supportive therapy control condition.…”
Section: Thoughts For Dougmentioning
confidence: 99%
“…The purpose of the evaluation was to (a) confirm eligibility, (b) determine initial tic severity, (c) establish the presence of comorbid conditions, and (d) document the type of VC and computer equipment being used by participants for the study. After eligibility was confirmed, a CBIT parent workbook (Woods et al, 2008) was mailed to families.…”
Section: Methodsmentioning
confidence: 99%
“…CBIT is a contemporary treatment program that incorporates early behavioral approaches (e.g., HRT) with other behavior therapy techniques. Recent multisite randomized controlled trials have demonstrated that CBIT is efficacious in both youth (Piacentini et al, 2010) and adults (Wilhelm et al, 2012), with treatment effects comparable to psychotropic medications, but without significant side effects (Scahill et al, 2013). In light of this strong efficacy data, CBIT has been disseminated through various avenues.…”
Section: ____________________________________________________________mentioning
confidence: 99%